Similarity Analysis between Scale Model and Prototype of Large Vibrating Screen - Zerong Zhang; Yongyan Wang; Zhimin Fan (Shock and Vibration)
In order to predict the physical characteristics of the large vibrating screen from its scale-down model, the similarity ratios of the frequency response functions, mode shapes, and dynamic stresses between the prototype and the scale model screen are built according to the similarity theory. The natural frequencies and modal shapes are extracted from the frequency response function by means of modal tests, in which the relative error of the natural frequencies is less than 9% and the modal shapes are consistent between the prototype and the model. The operating condition parameters including dynamic stress, displacement, velocity, and acceleration were also measured and conform to the similarity criteria. The results show that the inherent and operating condition parameters of the large vibrating screen can be obtained from the scale-down model conveniently, which provides an effective method for structural optimization and substructure coupling analysis of the large vibrating screen.